2005
DOI: 10.1111/j.1523-1755.2005.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum fetuin-A in nondialyzed patients with diabetic nephropathy: Relationship with coronary artery calcification

Abstract: This first study in early stages of diabetic chronic kidney disease shows that the role of serum fetuin-A may be far more complex than previously described. During predialysis stage of DN, there is a direct relationship between serum fetuin-A levels and CAC score. The reasons for this association in the presence of nephropathy are unclear, but may be secondary to proatherogenic insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
108
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 43 publications
14
108
0
3
Order By: Relevance
“…The positive correlation between circulating fetuin-A and cholesterol levels in this cohort was also observed in a cohort of 222 prevalent hemodialysis patients (32) and supports the link between fetuin-A and dyslipidemia (33,34). Possible factors accounting for this correlation include regular physical activity, which participates in the maintenance of low levels of circulating fetuin-A together with lower plasma cholesterol and enhanced insulin sensitivity (35), nutritional status (25), weight control, and amount of liver fat (36,37). The negative correlation between fetuin-A levels and history of smoking, which has not been reported before, may reflect the consequences of tobacco smoking on liver function, physical activity, and/or weight loss (38).…”
Section: Discussionmentioning
confidence: 93%
“…The positive correlation between circulating fetuin-A and cholesterol levels in this cohort was also observed in a cohort of 222 prevalent hemodialysis patients (32) and supports the link between fetuin-A and dyslipidemia (33,34). Possible factors accounting for this correlation include regular physical activity, which participates in the maintenance of low levels of circulating fetuin-A together with lower plasma cholesterol and enhanced insulin sensitivity (35), nutritional status (25), weight control, and amount of liver fat (36,37). The negative correlation between fetuin-A levels and history of smoking, which has not been reported before, may reflect the consequences of tobacco smoking on liver function, physical activity, and/or weight loss (38).…”
Section: Discussionmentioning
confidence: 93%
“…Patients on peritoneal dialysis with low fetuin-A levels showed a clear association with the MIA syndrome as well as with mortality and cardiovascular events [84] . Both coronary and aortic calcifications were found to be related to low fetuin-A levels and in patients with diabetic nephropathy, a positive association between fetuin-A levels and coronary calcification score was demonstrated [85][86][87] . The theory, that fetuin-A up-regulation may serve as a systemic defense mechanism to counteract early VCs, is supported by a study, where immunhistochemistry showed fetuin-A depositions around areas of VC, correlating well with the degree of calcification [85] .…”
Section: Fetuin-amentioning
confidence: 99%
“…It is emphasized that an elevated serum fetuin-A level is a sensitive marker of macrovascular complications in diabetics such as coronary atherosclerosis 3,7 . Moreover, Mehrotra et al observed higher serum concentration of fetuin-A among patients with advanced diabetic nephropathy (stages III and IV based on GFR) than in diabetics without kidney disease 41 . Lorant et al found that serum fetuin-A levels were higher in patients without renal disease and with type 2 diabetes and peripheral arterial disease (PAD) than those in individuals with type 2 diabetes and without PAD (ref.…”
Section: The Link Between Fetuin-a and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Singh et al suggested that the high concentrations of fetuin-A have been linked to cardiovascular complications in the non-renal patients 7 . In turn, Zhao et al reported that serum fetuin-A levels were independently associated with the presence and severity of coronary artery disease in participants with type 2 diabetes and Mehrotra et al described that fetuin-A concentrations were positively correlated with coronary artery calcifications in nondialized subjects with diabetic nephropathy 41,48 . On the other hand, some clinical studies have indicated the opposite trends-a decrease in fetuin-A levels have been associated with the presence of PAD in diabetics, an increased arterial stiffness, atherosclerotic plaque calcification and progression of cardiovascular disease 14,48 .…”
Section: Fetuin-a As a Marker Of Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation